Validation of cardiac damage classification and addition of albumin in a large cohort of patients undergoing transcatheter aortic valve replacement. (1st April 2020) - Berkovitch, Anat; Barbash, Israel M.; Finkelstein, Ariel; Assali, Abid R.; Danenberg, Haim; Fefer, Paul; Maor, Elad; Zhitomirsky, Sophia; Orvin, Katia; Zekry, Sagit Ben; Steinvil, Arik; Barsheshet, Alon; et al.
Abstract: Aims: We aimed to validate a new scoring system based on extent of cardiac damage for risk stratification in patients undergoing transcatheter aortic valve replacement (TAVR) in a real-world cohort and to examine the addition of baseline albumin in risk assessment. Methods and results: We investigated 2608 patients undergoing TAVR. Subjects were divided into five groups based on their echocardiography findings. Patients were further assessed by incorporating baseline albumin. Multivariable analysis demonstrated that each increase in stage was associated with significant increased risk of 1-year mortality (HR 1.37, 95%CI 1.23–1.54, p  < .001). Among patients at increased stage (3–4), incorporation of baseline of albumin identified the highest risk group, such that each 1 decrement in albumin levels was associated with more than triple increase in mortality among patients at stage 3 and 4 (HR 2.77, 95% CI 1.48–5.18, p -value = .001). Conclusions: Cardiac damage classification is validated in a real-world cohort of patients undergoing TAVR. Incorporation of low baseline albumin may further identify patients at the highest risk group. Condensted abstract: We evaluated 2608 patients undergoing transcatheter aortic valve replacement (TAVR) in order to validate a new scoring system dividing patients in to 5 stages (0–4) based on extent of cardiac damage. Patients were further assessed by incorporating baseline albumin. Multivariable analysis demonstrated that each increase in stage was associated with significant increased risk of 1-year mortality. Furthermore, among patients at increased stage (3–4), incorporation of baseline of albumin identified the highest risk group, such that each 1 decrement in albumin levels was associated with more than triple increase in mortality among patients at stage 3 and 4. Highlights: Pre-TAVR echocardiography is an independent factor for long term mortality. A recent staging system was proposed to assess patient's outcome post TAVR. The staging system was validated in a large, real-world cohort. Incorporation of low serum albumin improves the system accuracy. The staging system together with albumin identifies patients with futile prognosis.